2019
DOI: 10.1111/bju.14719
|View full text |Cite
|
Sign up to set email alerts
|

Pathological downstaging as a novel endpoint for the development of neoadjuvant chemotherapy for upper tract urothelial carcinoma

Abstract: Objectives To evaluate whether pathological downstaging (pDS) was more informative in predicting overall survival (OS) than pathological complete response (pCR) in patients treated with neoadjuvant chemotherapy (NAC) for upper tract urothelial carcinoma (UTUC). Patients and Methods The National Cancer Database was queried for patients with high‐grade cN0M0 disease who had received NAC. pDS was defined as a decrease of at least one stage from cT to pT stage along with pN0, including pCR. A multivariable Cox mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Recent studies have shown that NAC is associated with higher rates of pDS and pCR and improved RFS, CSS, and OS in patients with locally advanced or node-positive UTUC [15,16]. On the contrary, studies evaluating the role of NAC for localised or cN0M0 UTUC are insufficient [18,19]. To the best of our knowledge, this is the first report to identify the prognostic factors of high-risk UTUC after NAC, and the survival benefit of NAC for high-risk localised disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that NAC is associated with higher rates of pDS and pCR and improved RFS, CSS, and OS in patients with locally advanced or node-positive UTUC [15,16]. On the contrary, studies evaluating the role of NAC for localised or cN0M0 UTUC are insufficient [18,19]. To the best of our knowledge, this is the first report to identify the prognostic factors of high-risk UTUC after NAC, and the survival benefit of NAC for high-risk localised disease.…”
Section: Discussionmentioning
confidence: 99%
“…2A ). Several studies have suggested that pathological downstaging is a potential endpoint of NAC in UTUC [ 16 , 17 , 28 ]. However, difficulty in making an accurate T stage diagnosis is a strong limitation of pathological downstaging.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observations and results obtained through neoadjuvant chemotherapy in the treatment of bladder carcinoma, several retrospective studies have investigated the role of neoadjuvant therapy in UTUC. Utilizing preoperative cisplatin-based chemotherapy, pathological downstaging as well as lower recurrence rates and better outcomes have been observed (14,(89)(90)(91)(92). To date, no prospective trial has been published on this topic.…”
Section: Utuc In 2020mentioning
confidence: 99%